2014
DOI: 10.1109/tnano.2014.2303935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carrier Gas on the Growth and Characteristics of Spin-Capable Multiwalled Carbon Nanotubes

Abstract: Multiwalled carbon nanotube (MWCNT) sheets that can be spun directly from a spin-capable MWCNT forest promise novel applications that utilize the unique and outstanding characteristics of this material. The growth of spin-capable MWCNT forests will be achieved through the understanding of the important factors affecting the forest growth, since the precise conditions necessary for effective spin-capability are extremely sensitive. In this paper, we discuss the effect of carrier gas, the initial catalyst thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Our previous experiments produced transparent conductive CNT sheets by using a simple CNT spinning method. A 5–6-nm-thick iron film was deposited on a 330-μm-thick p-type silicon wafer using electrobeam (e-beam) evaporation. The thickness was monitored by a quartz-crystal sensor fixed inside the e-beam evaporation chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous experiments produced transparent conductive CNT sheets by using a simple CNT spinning method. A 5–6-nm-thick iron film was deposited on a 330-μm-thick p-type silicon wafer using electrobeam (e-beam) evaporation. The thickness was monitored by a quartz-crystal sensor fixed inside the e-beam evaporation chamber.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that Ar promoted the formation of longer and wider CNTs. Jung and Lee grew CNTs from C 2 H 2 on silicon (Si) substrates, in N 2 and He, and found that the generation of CNT forests was more likely to take place in N 2 than in He. The results of the aforesaid investigations suggest that the carrier gas type is an influential parameter in such processes, but they do not provide conclusive evidence on which gas is the most effective.…”
Section: Introductionmentioning
confidence: 99%